An Education System Worthy of Malaysia - M. Bakri Musa (Strategic Information Research Development, 2003)
Malaysia's highly centralized and tightly controlled system of education fails in educating and integrating the young. It is also ill suited for a plural society. Instead of the present rigid and uniform system, the writer calls for one that is flexible and diverse, but with a core commonality. There should also be private sector participation competition and spur innovation. Achieving this requires changing the ministry of education from one obsessed with strict top-down command, to a more democratized model with power and responsibilities delegated to the periphery. The minister is less a drill sergeant backing out orders to his raw recruits but more of a symphony conductor coaxing the best out of his skilled musicians. The reforms suggested here will make Malaysians fluently bilingual in Malay and English, science literate, and mathematically competent, as well as foster a common Malaysian identity.